PUBLIC PARTICIPATION IN URBAN PLANNING: GERMAN AND UKRAINIAN EXPERIENCE (Journal of Geography and Environmental Management, 2017)
Recently, the processes of direct implementation of power by the Ukrainian have become muchmore active in Ukraine, which, of course, should be welcomed, as it is evidence of further democratizationof state power and society as a whole. This also applies to the processes of city governance. In thisstudy, we want to show examples and problems of the participation of urban residents in the process ofcity-planning decision making in Ukraine and compare these processes with the situation in Germany,which is more elaborated in these processes. We will consider mechanisms for involving the public inUkraine and Germany. Community participation is realized in various forms: information, counseling,cooperation and delegation – to such an ideal we need to strive for Ukraine. It also substantiates theneed to increase the level of informing the population about the actions of the authorities in the regionand increase the institutional capacity to participate in them in accordance with the forms widely usedin the EU.